CORPORATE GOVERNANCE AND PROFITABILITY OF GENGHIS CAPITAL LIMITED IN NAIROBI CITY COUNTY - Malonza, Fiona Kanini; Mohinder, Prof. Jain (European Journal of Business and Strategic Management, 2019)
Purpose: The purpose of this study was to establish the effect of corporate governance on profitability; a study of Genghis Capital Limited, Nairobi. Methods: The study adopted a descriptive research design. The target population was 200 employees of Genghis Capital Limited. A stratified random sampling was used to select the sample. The sample size of the study was 107 employees. The study used questionnaires, containing both open ended and closed ended questions to obtain primary data. The questionnaires were self-administered. The instrument was also pretested with a sample of the respondents. The reliability of the instrument was estimated using Cronbach's Alpha coefficient. Pilot test was done by administering the instrument to ensure congruence between field objections and the phenomena being researched. Results: The results of the study indicated that board size, board independence, gender diversity, board competence are positively related with profitability. Board size, board independence, gender diversity, board competence were found to be satisfactory variables in explaining profitability. This is supported by coefficient of determination of 63.2%. Further, the results indicated that the overall model was statistically significant. This was supported by an F statistic of 40.418 and the reported p value (0.000) which was less than the conventional 0.05 significance level. Regression of coefficients results showed that board size, board independence, gender diversity, board competence and profitability are positively and significantly related. Unique Contribution to Theory, Practice and Policy: The study recommends that Genghis Capital limited incoporates these board characteristics by restructuring the board so that it can reflect features mentioned above. Basing on the discussion above, having a manageable board size, independent board, gender sensitive board and a competent board can lead an organization to prosperity.